THE FEASIBILITY ANALYSIS OF PURSE SEINE THE MOORING AT PELABUHAN PERIKANAN SAMUDERA (PPS) BUNGUS WEST SUMATRA PROVINCE - M. Hariski; Hendrik '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research on the feasibility analysis of purse seine the mooring at pelabuhan perikanan samudera (PPS) Bungus West Sumatra province, was conducted on November 2014. This research purpose is to know how big is the capital investment and how is the feasibility, sensitivity and prospects study of the purse seine 88 GT and the purse seine 117 GT. The method used in this research was survey method with respondents were selected through purposive sampling.The result of this research showed that the investment of the purse seine 88 GT was Rp. 794.250.000,- and the purse seine 117 GT was Rp. 1.057.650.000,- and the purse seine 88 GT operating expenses amount was Rp. 27.312.400,-/trip, and the purse seine 117 GT amount was Rp. 104.050.000,-/trip. Based of investment criteria to the purse seine 88 GT, the value of NPV was Rp. 1.864.167.579,-, the value of BCR was 1.26, and the value of IRR was >50%. While the purse seine 117 GT, the value of NPV was Rp. 3.245.547.895,-, the value of BCR was 1.36, and the value of IRR was >50%. It mean that the purse seine 88 GT and purse seine 117 GT is feasible to be developed but about is worth extended purse seine 117 GT more been extended then 88 GT, vessels seen from the feasibility analysis and sensitivity analysis.Keyword: purse seine 88 GT, purse seine 117 GT and feasibility study.